A Hódmezővásárhelyi országgyűlési képviselőválasztás 1935-ben - Zeman, Ferenc (Közép-Európai Közlemények, 2015)
In the spring of 1935 there was the general election in Hungary. At this time Gyula Gömbös was the Prime Minister of Hungary. The vote still passed off by the general election law of 1925. In the city of Hódmezővásárhely the election was secret and made with party lists. It was held at the end of April. In the course of the campaign three parties managed to have the enough recommendations: the Party of National Unity (with the leadership of András Tasnádi Nagy under-secretary for Religion and Education) the National Agricultural Opposition (with the leadership of Béla Kun) and the Hungarian Social Democratic Party (with the leadership of Ferenc Takács). The recommendation threshold was 10 percent of the number of all constituent, which was meant 1828 people in this case. In the course of the campaign all of the parties attacked each other in the pages of newspapers.The election ended in complete victory for the opposition. The vote result was a big surprise. The winner was in close fight the Hungarian Social Democratic Party. The second place was owned by the National Agricultural Opposition. The parliamentarian of the city became Ferenc Takács and Béla Kun. They both lived in Hódmezővásárhely.